IMPLEMENTASI SISTEM PROTEKSI PADA PLTS ON-GRID PADA RANCANGAN LABORATORIUM TEACHING FACTORY - Alfarizi, Mohamad Fadly; Abdillah, Muhamad Farid Abdillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of renewable energy technology, particularly on-grid solar power plants (PLTS), demands competent human resources in the design, installation, and protection of industrial systems. This requires laboratory facilities capable of representing real-world conditions. This research aims to design and implement a protection system for an on-grid solar power plant (PLTS) within a Teaching Factory laboratory design to ensure the safety of equipment, users, and system reliability. The method used requires protection based on electrical installation standards, design of DC and AC side protection systems, and simulation and testing of protection performance. The implemented protection system includes the use of MCBs, DC fuses, surge protection devices (SPDs), an over/under voltage relay, and a grounding system. The design results demonstrate that the integrated protection system minimizes the risk of disturbances such as short circuits, overloads, voltage surges, and PLN grid disruptions, while also enhancing safety in the laboratory environment. The implementation of this protection system not only supports the technical operational aspects of on-grid solar power plants but also serves as a practical learning tool for students in understanding the safety and reliability standards of solar-based electric power systems. Thus, a Teaching Factory laboratory design equipped with an adequate protection system can provide an effective, safe, and industry-appropriate learning environment.